Pragmatics and Pedagogy: Illocutionary Acts in “Jackie” Movie and their Merdeka Belajar Curriculum Relevance - Zelfany Lufti Milinia Adira Putri; Wiwin Widyawati (Aqlamuna: Journal of Educational Studies, 2024)
Illocutionary acts, as theorized by Kent Bach, play a crucial role in daily communication by conveying the speaker's intent beyond mere words. These big four acts, which include Constative, Directives, Commisives, and Acknowledgement, help people understand the social and pragmatic context of interactions where in Merdeka Belajar Curriculum, which emphasizes independence and critical thinking in education, understanding illocutionary acts can be linked to social norms by fostering effective communication skills. Students learn to interpret and employ various speech acts appropriately, aligning their verbal interactions with societal expectations and cultural norms.The study aims to analyze the illocutionary acts used by the main character in the movie "Jackie" by LD Entertainment, with a focus on the pragmatic aspects of speech acts within the movie dialogues. This study used the mixed of Qualitative-descriptive research as methodology with Library research as the design. Then, the primary objectives are to identify the types of illocutionary acts employed by the character and to explore their relationship with social norms as outlined in the Merdeka Belajar Curriculum. The research employed a content analysis methodology, analyzing conversational fragments from the movie to categorize various illocutionary acts based on Kent Bach’s theory. The data were collected from the "Jackie" movie script and by watching the movie, where the results became the next data to analyze the links between the illocutionary utterances and social norms such as religious norms, legal norms, ethical norms, and etiquette norms.The results showed that there are four main types of illocutionary acts found in the movie "Jackie" based on Kent Bach’s Theory such as : (1)Constatives, where the speaker expresses a belief and intends for the hearer to form a similar belief; (2)Directives, which express the speaker's attitude toward some prospective actions by the listener and the intention for the listener to consider the statement as a reason for their actions; (3)Commisives, which involve the speaker obligating themselves or proposing to do something specified in the propositional content; and (4)Acknowledgements, which express feelings about the listener or interlocutor, often in a perfunctory or formal manner. These categories contain a large number of sub-types. Additionally, the results discovered several phrases related to social norms in the Merdeka Belajar Curriculum using illocutionary speech actions theory, including religious norms, legal norms, ethical norms, and etiquette norms.